Sistem Penunjang Keputusan Seleksi Calon Karyawan Menggunakan Metode SAW (Simple Additive Weighting) Pada PT. Delta Kristalis - P, Megawati; Allwine; Tarigan, Irwan Jani (Jurnal Mahajana Informasi, 2022)
Selection of prospective employees is one of the processes carried out to screen prospective employees to fill the required job vacancies. PT. Delta Kristalis is a company that often selects prospective employees. Based on the current prospective employee selection system, it is less efficient in the screening process for prospective employees. So that the selection and evaluation process for prospective employees can be carried out efficiently at PT. Delta Kristalis, it is necessary to develop a decision support system by implementing the SAW method. The decision support system to be developed is web-based using programming languages.PHP and Mysql as databases so that it becomes a website that can run properly. The criteria used are work experience, last education, age, domicile, and requested salary. The implemented decision support system can present the ranking of the results of the selection so that it can help stakeholders to make decisions on the acceptance of prospective employees.